A transport policy tool for reduction of CO2 emissions in Finland – Visions, scenarios and pathways using pluralistic backcasting method - Tuuli Järvi; Anu Tuominen; Petri Tapio; Vilja Varho (Elsevier, 2022)
The reduction of greenhouse gas emission was the basis of a Delphi study where expert opinions about future development were asked and used to form visions of the future, and further elaborated to scenarios using a pluralistic backcasting method. A new innovative approach on how to use and combine methods and data from various disciplines in scenario modelling, on transport policy packaging and determining pathways to reach the desired futures, is presented for two of the visions analysed in detail. This paper focuses on the diverse methods and data used while the scientific background of the backcasting method has already been published in Tuominen et al. (2014).